2020
DOI: 10.1002/jbmr.4796
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Lipidomic Profiling of Mouse Joint Tissue Demonstrates the Essential Role of PHOSPHO1 in Growth Plate Homeostasis

Abstract: Lipids play a crucial role in signaling and metabolism, regulating the development and maintenance of the skeleton. Membrane lipids have been hypothesized to act as intermediates upstream of orphan phosphatase 1 (PHOSPHO1), a major contributor to phosphate generation required for bone mineralization. Here, we spatially resolve the lipid atlas of the healthy mouse knee and demonstrate the effects of PHOSPHO1 ablation on the growth plate lipidome. Lipids spanning 17 subclasses were mapped across the knee joints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…25 Bone homeostasis is a complex sequence of bone resorption and bone formation and integrity of bone tissue are maintained by various factors such as BMSCs, 26 osteoclasts and osteoblasts, 27 macrophages, 3 blood vessels, 28 or calcium ions. 29 Oxidative stress can cause potentially harmful effects on cells, such as protein oxidation or oxidative DNA damage, which are considered crucial reasons in triggering various pathologic changes related to tissue injury, 30 including OP. 4 Accumulating evidence demonstrated that oxidative stress is often accompanied by an increase in ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Bone homeostasis is a complex sequence of bone resorption and bone formation and integrity of bone tissue are maintained by various factors such as BMSCs, 26 osteoclasts and osteoblasts, 27 macrophages, 3 blood vessels, 28 or calcium ions. 29 Oxidative stress can cause potentially harmful effects on cells, such as protein oxidation or oxidative DNA damage, which are considered crucial reasons in triggering various pathologic changes related to tissue injury, 30 including OP. 4 Accumulating evidence demonstrated that oxidative stress is often accompanied by an increase in ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, osteoporotic fracture has become a global health problem, leading to a significant reduction in quality of life and huge socio‐economic burden 25 . Bone homeostasis is a complex sequence of bone resorption and bone formation and integrity of bone tissue are maintained by various factors such as BMSCs, 26 osteoclasts and osteoblasts, 27 macrophages, 3 blood vessels, 28 or calcium ions 29 . Oxidative stress can cause potentially harmful effects on cells, such as protein oxidation or oxidative DNA damage, which are considered crucial reasons in triggering various pathologic changes related to tissue injury, 30 including OP 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the profound diversity of lipid structures and their multilevel spatial and dynamic complexity, a thorough examination of lipid composition with their spatial distribution in tissue would enhance our understanding of their physiological significance. Currently, spatially resolved lipidomics has been widely used to reveal tissue-specific lipid metabolism changes in cerebral ischemia, nonalcoholic fatty liver, renal cell carcinoma, and others. …”
mentioning
confidence: 99%
“…Phospho1 is proposed to operate within MVs by generating Pi from the hydrolysis of phosphocholine (PC) and phosphoethanolamine (PE) 134 . A recent study employing spatial metabolomics in mice growth plate confirmed the involvement of lipid metabolites related to PC and PE in mineralizing regions 135 . An intriguing discovery from a spectroscopic study is that choline can be integrated into the bone mineral, providing further evidence for their involvement in bone mienralization 136 .…”
Section: The Structure and Formation Of Bone Tissuementioning
confidence: 91%